Disturbance decoupled fault reconstruction using sliding mode observers - Kok, Yew Ng; Chee, Pin Tan; Akmeliawati, Rini; Edwards, Christopher (Wiley Online Library, 2010)
This paper investigates and presents conditions that guarantee disturbance decoupled fault reconstruction using sliding mode observers, which are less stringent than those of previous work, and show that disturbance reconstruction is not necessary. An aircraft model validates the ideas proposed in this paper.